Urbanizing Indonesia Trends and Challenges of Urbanization in 21 st Century - Achmad Nurmandi (University of Western Australia, 2011)
This paper aims to explore the trends and challenges of urbanization in Indonesia until 2050. The paper uses Central Bureau of Statistics data to make a projection to 2050. The available data indicate that by 2050 the island of Java will be urban. From 1961 to 2005, the growth rate of living in urban areas in Indonesia increased rapidly. In the period 1961-1970, the national population growth rate was 2.2% per year, compared with growth in cities of 2.6% per year. In the period 1970-1980, the population growth rate was 2.06%, and it decreased again in the period 2000-05. Conversely, the number of people living in urban areas experienced significant growth, from 2.6% in the period 1961-1970 to 5.89% in the period 2000-2005. Rapid urban growth has directly impacted the development of basic infrastructure and public services in urban areas in Indonesia. Lack of clean water, housing and employment, along with poor sanitation and adequate transportation to meet the needs of urban population growth, are problems faced in urban Indonesia in the 21st century.